The Role of cAMP-PKA Pathway in Lactate-Induced Intramuscular Triglyceride Accumulation and Mitochondria Content Increase in Mice - Chen, Siyu; Zhou, Lei; Sun, Jingquan; Qu, Yaqian; Chen, Min (Frontiers in Physiology, 2021)
The glycolytic product of exercise, lactate, has long been recognized to promote lipid accumulation by activation of G-protein-coupled receptor 81 (GPR81) and inhibition of the cyclic adenosine monophosphate-protein kinase A (cAMP –PKA) pathway in adipose tissue. Whether lactate causes a similar process in skeletal muscle is unclear. Lactate might also improve mitochondria content in skeletal muscle; however, the mechanism is not clarified either. In this study, using intramuscular injection of lactate to the gastrocnemius and intraperitoneal injection of forskolin (activator of cAMP-PKA pathway), we identified the role of the cAMP-PKA pathway in lactate-induced intramuscular triglyceride accumulation and mitochondrial content increase. The intramuscular triglyceride level in the gastrocnemius increased after 5weeks of lactate injection (p<0.05), and this effect was blocked by forskolin injection (p<0.05). Corresponding expression level changes of GPR81, P-PKA/PKA, P-CREB/cAMP-response element binding protein (CREB), and proteins related to lipid metabolism suggest that lactate could induce intramuscular triglyceride accumulation partly through the inhibition of the cAMP-PKA pathway. Meanwhile, the intramuscular expression of citrate synthase (CS) and the activity of CS increased after 5weeks of lactate injection (p<0.05), but the change of CS expression was not blocked by forskolin injection, suggesting other mechanisms might exist. Consequently, exploration for other potential mechanisms that might contribute to the lactate-induced mitochondria content increase was conducted. We found an increase in the contents of lactate-related metabolites in skeletal muscle mitochondria after acute lactate injection (the p-value of each analysis is less than 0.05). LHDA was also validated to exist in mitochondria in this study. These results provide a possibility for metabolism-related mechanisms of lactate-induced mitochondria content increase. Future study is needed to validate this hypothesis. In conclusion, lactate-induced intramuscular triglyceride accumulation is achieved by inhibition of lipolysis, and this process is regulated by the cAMP-PKA pathway. Promoted lipogenesis also contributes to lactate-induced triglyceride accumulation, and this process might also be regulated by the cAMP-PKA pathway. Lactate injection might increase mitochondria content and cAMP-PKA pathway might have a limited contribution, while other metabolism-related mechanisms might play a prominent role.